On the Paper: ''Examples in Cone Metric Spaces: A Survey'' Middle East Journal of Scientific Research, 11(12):1636-1640, 2014, M. Asadi, H. Soleimani - Abdallah A. Hakawati (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The paper ''Examples in Cone Metric Spaces: A Survey'' had overlooked the fact that -spaces are Banach spaces only for . Here, we show that, for , is not even a normed space .We also pointed out that the domain of the function of Example (1.17) of the paper ''Examples in Cone Metric Spaces: A Survey'' does not allow the cone metric to be defined, so we made two possible alternatives for that to make sense. Furthermore, we give a few remarks on cone metrics and cone norms which were not fully dealt with in the literature.